Philosophical Values of the Sedulur Sikep (Samin Tribe) of Bojonegoro: Contextual Resources for Mathematics Learning - Dwi Erna Novianti; Puput Suriyah; Ari Indriani; Nurul Nadiya Abu Hassan (Hipotenusa: Journal of Mathematical Society, 2026)
This study aims to identify the philosophical values embedded in the Sedulur Sikep (Samin) community in Bojonegoro and reconstruct them into a contextual mathematics learning design. The study employed a qualitative ethnographic approach involving six participants, consisting of community leaders and members selected purposively based on their knowledge of Sedulur Sikep teachings and practices. Data were collected through participant observation, in-depth interviews, and document analysis. Data analysis was conducted using open coding, thematic categorization, and interpretive analysis to examine the relationship between cultural values and mathematics learning contexts. The findings indicate that the values of ora jumput (not taking others’ rights), ora bedok (honesty), and ora srei (not being greedy) function as ethical principles consistently reflected in social practices related to resource management, economic interactions, and everyday decision-making. These values were reconstructed into authentic contexts for mathematics learning through tasks involving fair distribution, procedural consistency, and decision-making under constraints. The integration of cultural values was framed through Contextual Teaching and Learning (CTL) and Realistic Mathematics Education (RME), positioning cultural practices as starting points for mathematical activity. The contribution of this study lies in proposing a learning design framework that connects Sedulur Sikep philosophical values with operational mathematical contexts. The findings extend ethnomathematics research beyond cultural identification toward the reconstruction of cultural values as resources for contextual mathematics learning design.